INVESTIGATING THE EFFECTIVENESS OF PROJECT BASED LEARNING WITH TIKTOK APP ON STUDENTS’ SPEAKING OUTCOME - Rahmah Julianti; Dian Fera Pratiwi (EDU RESEARCH, 2023)
This paper focuses on the problem of classroom teaching and learning through classroom action research. The students’ speaking ability, diagnostic test and the implementation of Project-based learning led to this study. This research aims to investigate the effectiveness of PjBL with Tiktok app on students’ speaking outcome. The subjects of this study were 36 first grade senior high students of SMAN 13 Makassar in academic year 2022/2023. The learning outcome shows the improvement of the students’ speaking ability after cycle I and cycle II have been conducted. Increased numbers of students achieved the basic completeness requirement shows the improvements in their speaking ability. The proportion of students who managed to pass was 86 % in cycle I. The mean score from 70.0 in the pre-cycle to 80.7 in cycle I. The trend persists into cycle II, where the mean score increases to 84 and the proportion of students who passed rises to 94% with some students categorized as excellent.